(untitled) (Medical Forum Monthly, 2024)
Objective: The frequency of Urinary tract infections (UTI) amongst neonates having asymptomatic jaundice. Study Design: cross sectional study. Place and Duration of Study: This study was conducted at the Paediatrics Department of Services Hospital, Lahore from August 2018 to March 2019. Materials and Methods: We enrolled 160 neonates with asymptomatic jaundice having no history of fever from last 2 weeks. Frequency of UTI was noted among all the study participants. All the information regarding this study was noted on a predesigned proforma. SPSS version 21 was used for data entry and analysis for this study. Chi square test was used to see any difference of study variables among the study participants with or without UTI and p value < 0.05 was taken as significant. Results: Amongst a total of 160 neonates, there were 89 (55.6%) male and 71 (44.4%) female. Overall, mean age was found to be 20 days with a standard deviation of 3.8 days. Most of the children, 93 (58.1%) were between the age of 21 to 28 days while remaining 67 (41.9%) 14 to 21 days. UTI was present in 15 (9.4%). The most common pathogen involved in UTI was E. Coli in 6 (40.0%), klebsiella in 4 (26.7%), staph epidermidis in 2 (13.3%), enterobacter in 2 (13.3%) and pseudomonas in 1 (6.7%). Conclusion: UTI is common in neonates having afebrile asymptomatic jaundice. Commonest pathogens involved are E.coli and klebsiella. Asymptomatic neonates presenting with jaundice should be given special attention to rule out UTI for the early diagnosis and management.